Direct evidence of barrier inhomogeneities at metal/AlGaN/GaN interfaces using nanoscopic electrical characterizations. (6th June 2017) - Kumar, Ashutosh; Kapoor, Raman; Garg, M; Kumar, V; Singh, R
Abstract: The existence of barrier inhomogeneities at metal–semiconductor interfaces is believed to be one of the reasons for the non-ideal behaviour of Schottky contacts. In general, barrier inhomogeneities are modelled using a Gaussian distribution of barrier heights of nanoscale patches having low and high barrier heights, and the standard deviation of this distribution roughly estimates the level of barrier inhomogeneities. In the present work, we provide direct experimental evidence of barrier inhomogeneities by performing electrical characterizations on individual nanoscale patches and, further, obtaining the magnitude of these inhomogeneities. Localized current–voltage measurements on individual nanoscale patches were performed using conducting atomic force microscopy (CAFM) whereas surface potential variations on nanoscale dimensions were investigated using Kelvin probe force microscopy (KPFM) measurements. The CAFM measurements revealed the distribution of barrier heights, which is attributed to surface potential variations at nanoscale dimensions, as obtained from KPFM measurements. The present work is an effort to provide direct evidence of barrier inhomogeneities, finding their origin and magnitude by combining CAFM and KPFM techniques and correlating their findings.